School Culture and the Performance of Islamic Religious Education Teachers in Forming Students' Religious Behavior at Islamic High School 1 Surakarta - Gali Nurma Saudi; Muhammad Ja’far Nashir (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to analyze the influence of school culture and Islamic Education (PAI) teacher performance on the religious behavior of students at SMA Islam 1 Surakarta in the 2024/2025 academic year. Phenomena in the field show challenges in students' religious behavior, such as low discipline in worship and rudeness in speech. This research is quantitative in nature, using multiple linear regression analysis. The research population includes all 90 students in grade XI, with sampling using the saturated sample or census method. Data were collected through Likert scale questionnaires, observation, and documentation. The partial results of the study show that: (1) School culture has a positive and significant effect on students' religious behavior with a significance value of 0.001 < 0.05 and a contribution of 31.5%; (2) PAI teacher performance has a positive and significant influence on students' religious behavior with a significance value of 0.006 < 0.05. Simultaneously, the better the implementation of school culture and PAI teacher performance, the higher the quality of students' religious behavior in the school. This study recommends the importance of strengthening religious culture and optimizing the role of teachers as role models in shaping students' spiritual character.